Individual Differences in Academic Delay of Gratification - Bembenutty, Hefer; Karabenick, Stuart A. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This study examined the relationship between college students' preference for an immediately available option (e.g., go to a favorite concert the day before a test) or a delayed alternative (e.g., stay at home to study for the test). Analysis focused on how much a student would like to engage in a specific activity, the importance of the activity to him/her, and the student's academic expectations given a choice for each activity. Undergraduate college students (n=113) completed the academic delay of gratification (ADOG) scale, in which students choose between an attractive, immediately available option versus a delayed alternative likely to produce better academic achievement. Students also completed the motivated strategies for learning questionnaire, which assesses students' motivational tendencies, cognitive strategies, and self-regulatory learning strategies. Analysis found that delay of gratification was a direct function of the differences between liking for, value of, and expectancy of academic success given the option of an immediate pleasurable activity. Motivation for learning and use of learning strategies were also functions of these differences. Results support the view that academic delay of gratification is an important volitional and self-regulatory strategy employed by learners to obtain academic achievement. The ADOG scale is appended. (Contains 16 references.) (DB)
ERIC Note: Paper presented at the Annual Meeting of the Eastern Psychological Association (Boston, MA, February 1998). For related papers, see HE 031 525-526.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Students; Delay of Gratification; Goal Orientation; Higher Education; Individual Differences; Learning Motivation; Questionnaires; Student Educational Objectives; Time Factors (Learning); Academic Delay of Gratification Scale -- Choice Behavior; Motivated Strategies for Learning Questionnaire; Reports, Research; Speeches/Meeting Papers; Tests/Questionnaires.